2015
DOI: 10.5604/20831862.1174771
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of aerobic capacity, anaerobic peak power and experience to performance in HIT exercise

Abstract: CrossFit is becoming increasingly popular as a method to increase fitness and as a competitive sport in both the Unites States and Europe. However, little research on this mode of exercise has been performed to date. The purpose of the present investigation involving experienced CrossFit athletes and naïve healthy young men was to investigate the relationship of aerobic capacity and anaerobic power to performance in two representative CrossFit workouts: the first workout was 12 minutes in duration, and the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
166
3
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(194 citation statements)
references
References 14 publications
(19 reference statements)
8
166
3
17
Order By: Relevance
“…In contrast to these studies, our findings show that there are significant associations between aerobic (i.e., VO 2max ) and anaerobic capacity (i.e., peak power), in addition to whole-body muscular strength, with work capacity performance. Findings from Bellar et al [21] support these associations as they also show aerobic and anaerobic capacity relate to select modes (i.e., WOD selection and/or style) of work capacity performance. One reason for these differences in association could be the homogeneity of the respective study populations.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to these studies, our findings show that there are significant associations between aerobic (i.e., VO 2max ) and anaerobic capacity (i.e., peak power), in addition to whole-body muscular strength, with work capacity performance. Findings from Bellar et al [21] support these associations as they also show aerobic and anaerobic capacity relate to select modes (i.e., WOD selection and/or style) of work capacity performance. One reason for these differences in association could be the homogeneity of the respective study populations.…”
Section: Discussionmentioning
confidence: 91%
“…CrossFit is a sport that includes a wide variety of generally short-duration, high-intensity exercises ranging from Olympic weight lifting to rowing exercises. Performance in this sport is highly dependent on peak power and fatigue resistance [12]. As such, dietary nitrate may be beneficial for CrossFit athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In this line of research, Butcher (17) conducted a study with CF Regionals and Open level competitors where he showed that performance in tests such as VO2max and Wingate were not correlated with performance in standard CF workouts, although correlation between Fran and Grace (CF's most common benchmark routines) and whole-body strength (1RM tests in specific exercises) tests was reported. In a study of 32 trained individuals, separated in two groups, with and without CF experience, Bellar (18) , found similar results.…”
Section: Introductionmentioning
confidence: 70%